EXPRESSIVE SPEECH ACT AS FOUND ON LA LA LAND MOVIE - Royanti Royanti (Politeknik Negeri Bengkalis, 2019)
In analyzing utterances there are some branches of pragmatics that we can used, one of them is speech act. Speech act is language cover an action. Speech act divided into 3 levels; locutionary act, illocutionary act and perlocutionary act. This research tells about illocutionary act especially expressive act. Expressive act is what the speaker feels about state of affair in sincerity condition and the social relationship between speaker and the hearer in society is social function. Research questions of this study were: (1) what are the types of expressive speech acts as found on La La Land movie, (2) What are the social functions of expressive speech acts as found on Lala Land movie. The researcher used qualitative approach. The researcher was used Lala Land transcript as a media to collect the data. The data of this research are the utterances containing expressive speech act taken from the conversation between characters in the La la Land movie. The researcher used content analysis, the data are in the form of the script of Lala Land dialogue. In analyzing the data, the researcher used Searle (1976) and Norrick’s (1978) theories. The result of this showed that there are 35 utterances consist of expressive speech act. All of the types were appear except expressive act of condoling and classified into theirs social function.In analyzing utterances there are some branches of pragmatics that we can used, one of them is speech act. Speech act is language cover an action. Speech act divided into 3 levels; locutionary act, illocutionary act and perlocutionary act. This research tells about illocutionary act especially expressive act. Expressive act is what the speaker feels about state of affair in sincerity condition and the social relationship between speaker and the hearer in society is social function. Research questions of this study were: (1) what are the types of expressive speech acts as found on La La Land movie, (2) What are the social functions of expressive speech acts as found on Lala Land movie. The researcher used qualitative approach. The researcher was used Lala Land transcript as a media to collect the data. The data of this research are the utterances containing expressive speech act taken from the conversation between characters in the La la Land movie. The researcher used content analysis, the data are in the form of the script of Lala Land dialogue. In analyzing the data, the researcher used Searle (1976) and Norrick’s (1978) theories. The result of this showed that there are 35 utterances consist of expressive speech act. All of the types were appear except expressive act of condoling and classified into theirs social function.